Dynamic characterization of MEMS diaphragm using time averaged in-line digital holography - Miao, Jianmin (2011)
In this paper dynamic characterization of a MEMS diaphragm is investigated using lens-less time averaged in-line digital holography. The analysis and capability of the numerically reconstructed amplitude and phase information from in-line time averaged holograms as applied to MEMS vibration are presented. Particularly the effect of mean static state on the phase in time averaged digital holography is explored. A novel double exposure method is also demonstrated using a diverging object wave suitable for dynamic characterization of small size objects. A phase jump in the static deformation fringes in the vibrating regions is observed and described and can be used for precise analysis of vibration mode shape under simultaneous presence of mean static deformation. A simple and robust tool for dynamic optical metrology of MEMS devices and micro-objects using time averaged in-line digital holography is thus proposed.